2009
DOI: 10.1016/j.joca.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Local cytokine profiles in knee osteoarthritis: elevated synovial fluid interleukin-15 differentiates early from end-stage disease

Abstract: IL-15 is elevated in early knee OA, suggesting activation of an innate immune response in the SM. The association of IL-15 expression with CD8 transcripts and MMPs implicates this cytokine in OA pathogenesis and as a candidate therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
183
5
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(205 citation statements)
references
References 48 publications
13
183
5
4
Order By: Relevance
“…[79][80][81] In contrast, the two cytokines for which we observed differences between the OAC-AM and NC-AM group -namely IL-6 and IL-8 -have been demonstrated to increase in late versus early shoulder OA. 82 Combined, these points of comparison of NC-AM to OAC-AM to human disease suggest that our OAC-AM system may be serving as a disease mimic for later stage OA than the NC-AM system.…”
Section: Discussioncontrasting
confidence: 65%
“…[79][80][81] In contrast, the two cytokines for which we observed differences between the OAC-AM and NC-AM group -namely IL-6 and IL-8 -have been demonstrated to increase in late versus early shoulder OA. 82 Combined, these points of comparison of NC-AM to OAC-AM to human disease suggest that our OAC-AM system may be serving as a disease mimic for later stage OA than the NC-AM system.…”
Section: Discussioncontrasting
confidence: 65%
“…This eventually leads impaired ECM synthesis, cartilage degradation and, ultimately, development of OA [36,37].…”
Section: Page 6 Of 39mentioning
confidence: 99%
“…A variety of animal OA models with ACL transection have shown upregulation of genes coding for aggrecanases and MMPs as well as increased concentrations of these destructive proteases [1,10,20,47]. Most human studies demonstrate elevated MMPs and aggrecan degradation in patients with OA as compared with healthy control subjects and that these proteases are more elevated in patients with end-stage OA compared with early OA [4,21,23,28,34]. In an effort to look specifically at the presence of proteolytic enzymes after traumatic injury, several authors have shown elevated MMPs and aggrecan degradation after ACL tear.…”
Section: Introductionmentioning
confidence: 99%